Presynaptic NMDA receptors and spike timing-dependent long-term depression at cortical synapses - Rodriguez Moreno, Antonio; Banerjee, Abhishek; Paulsen, Ole (Frontiers in Synaptic Neuroscience, 2010)
It has recently been discovered that some forms of timing-dependent long-term depression (t-LTD) require presynaptic N-methyl-D-aspartate (NMDA) receptors. In this review, we discuss the evidence for the presence of presynaptic NMDA receptors at cortical synapses and their possible role in the induction of t-LTD. Two basic models emerge for the induction of t-LTD at cortical synapses. In one model, coincident activation of presynaptic NMDA receptors and CB1 receptors mediates t-LTD. In a second model, CB1 receptors are not necessary, and the activation of presynaptic NMDA receptors alone appears to be sufficient for the induction of t-LTD.